2010
DOI: 10.1149/1.3484797
|View full text |Cite
|
Sign up to set email alerts
|

Behavior of Molybdenum Chloro-Species in Alkali Chloride-Based Melts: Implications for Spent Nuclear Fuel Treatments

Abstract: Chloro-species of molybdenum in oxidation states (III), (IV) and (V) were studied in a range of alkali chloride melts employing high temperature electronic absorption spectroscopy. The reaction rates of disproportionation of MoCl63- complex ions in various melts between 550 and 750 oC were determined. Mo(IV) species MoCl62- were generated and thermodynamic properties of Mo(IV) chloride in NaCl-CsCl eutectic melt estimated. Absorption spectra of molybdenum(V) MoCl6- were measured in a chloride melt for the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…33,34 Previous high temperature spectroscopy studies showed that six-coordinated MoCl 6 3ions were formed in the melt irrespectively of the method used for introducing molybdenum ions (anodic dissolution of the metal or dissolution of K 3 MoCl 6 ). 31,35 The concentration of molybdenum in the quenched melt samples was determined photometrically with thiocyanate. 36 Volumetric analysis (oxidimetric titration) was employed to estimate the mean oxidation state of molybdenum in the quenched melts.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…33,34 Previous high temperature spectroscopy studies showed that six-coordinated MoCl 6 3ions were formed in the melt irrespectively of the method used for introducing molybdenum ions (anodic dissolution of the metal or dissolution of K 3 MoCl 6 ). 31,35 The concentration of molybdenum in the quenched melt samples was determined photometrically with thiocyanate. 36 Volumetric analysis (oxidimetric titration) was employed to estimate the mean oxidation state of molybdenum in the quenched melts.…”
Section: Methodsmentioning
confidence: 99%
“…Melts containing Mo(IV) ions can be obtained by reacting MoO 2 with hydrogen chloride. 31 Our previous spectroscopic and spectroelectrochemistry studies showed that Mo(IV) chloro-species are most stable at lower temperatures and in the melts containing low ionic momentum cations (cesium). 31 Electronic absorption spectroscopy allowed clear distinction between Mo(III) and Mo(IV) ions.…”
Section: Stability Of Mo(iii) Ions In Chloride Melts-electronic Absor...mentioning
confidence: 99%
See 2 more Smart Citations
“…[1][2][3][5][6][7][8][9][10][11][12] Especially the molybdenum with high-field strength (F = Z/d 2 ), one of the main fission products (~10 wt%) in HLW produced during spent fuel reprocessing process has a very low solubility (~1 mol%). 13 niobyl(3+) cation (NbO 3+ ), which enters deform dra (octahedra, tetragonal pyramids) with a co covalent bond to oxygen. 16,17 2 | METHOD 2.1 | Thermodynamic model of…”
Section: Introductionmentioning
confidence: 99%